Approximate Solving of the Third Boundary Value Problems for Helmholtz Equations in the Plane with Parallel Cuts - Dushkin, V.D. (Журнал математической физики, анализа, геометрии, 2017)
In the paper, the method of approximate solution of boundary integral equations of the original problem is proposed. The systems of boundary integral equations of the problem are obtained by the method of parametric representation of integral transforms. The convergence of approximate solutions to the exact solution of the original problem is guaranteed by the propositions proved in the paper. Also, the rate of convergence of approximate solutions to exact solutions is found.